Responsabilidad ambiental en hoteles de la ciudad de Babahoyo - Acosta Cedeño, Esther Andreina (2018)
This Project talks about ENVIRONMENTAL RESPONSIBILITY IN THE HOTELS CACHARÍ AND GREEN PEARL OF THE CITY OF BABAHOYO, because in these establishments there is little knowledge about the environmental responsibility on the part of the owners, which is a very important issue because it depends on this good customer service, and that this establishment is considered a pleasant place to rest. Having no knowledge of this issue, it gives way to Environmental Irresponsibility That is why to improve this problem it is recommended in this Project: Conduct awareness talks teaching new environmental practices including solid waste management, saving water and energy. For this work interviews were used, and surveys were carried out to the guests and citizens in general to determine the situation of the place and what is required for the solution of the problem having as main objective the ENVIRONMENTAL RESPONSIBILITY.